غريب اللغة بين التقييد والإبتذال - كاظم فضيل شاهر, أ.م. د (lark, 2021)
The strange language is the wards and expressions that are vaque and far from understanding the strange expressions in the eras of protest was eloquent for those who say and transporters. But it lost that after the ages of protest during the time of the moderns so he took the meanings of the rare and the vulgar which is spoken by other than the eloquent, the ignorant, the people of the professions and the craftsmen. It became alot of use and it is not eloquent often.